Ḥȋlah Dalam Fatwa DSN-MUI Tentang Dana TBDSP Bagi Lembaga Keuangan Syariah - Hasim Hasim; Muhajir Muhajir; Achmad Nursobah (CV. ULIL ALBAB CORP, 2024)
The use of new transactions in Islamic finance has faced criticism, particularly regarding the implementing of ḥȋlah (legal stratagem) which is seen as adopting conventional financial instruments that go against religious morals. This research examines the application of ḥȋlah in the Indonesian Ulama Council's (DSN-MUI) fatwa, or religious ruling, on funds that are not considered to be halal (funds that cannot be recognized as income). A way to divide up accounts and direct non-halal money toward social causes is offered by the DSN-MUI. Using a normative-philosophical perspective, this study reveals how ḥċlah is applied in the fatwa. The results show indications of the application of ḥȋlah, as seen from: (1) the recognition of non-halal funds, (2) the obligation to have a special account to separate halal and non-halal funds, and (3) the distribution of non-halal funds for socio-religious activities as an effort to avoid the stagnation of wealth. Overall, this fatwa tends to use ḥȋlah by referring to the practice of the Prophet Muhammad in handling assets with unclear legal status.